Critical Assessment of Three Decades of Breast Cancer Research in Yemen: Systematic Review (Medico Legal Update, 2021)
Objective: The aim of this review is to critically assess three decades (1989 to 2019) of breast cancerresearch in Yemen and to identify the gaps in, and need for, breast cancer research in Yemen.Methodology: A search was performed in Web of Science, EMBASE, PubMed, Google Scholar and Ovidto identify articles on breast cancer research in Yemen that were published in the last three decades. Thearticles were selected and reviewed by experts in this field, based on clinical relevance and future researchimplications.Results: This review comprised 19,031 participants, extracted from 27 articles that were included andanalyzed. Breast cancer patients in Yemen were commonly diagnosed at an early age of 50 years or younger.Overall, awareness of breast cancer among Yemeni women was very poor. Some studies reported that a lowrate of only 11%-17.4% of Yemeni women practiced breast screen examination. Only 1.6% of the Yemeniwomen had been screened by a mammogram test. The highest performed surgery was a modified radicalmastectomy (N=211). The highest cases of breast cancer were reported in Hadramout (N=956) and the mostcommon histological subtype was invasive ductal carcinoma (N=2695).Conclusions: Yemen is characterised by three decades of scattered, fragmented and poor quality breastcancer research. Therefore, there is a need to establish a breast cancer research center in Yemen to researchall aspects of breast cancer in Yemen, and to build bridges for collaborations in breast cancer researchglobally.